PEMBERIAN SUMBANGAN KEPADA PARA PEMINTA-MINTA PASCA PANEN PADI - zalikha zalikha (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2016)
One of social and religious problems the issue related to beggar (or well known as gepeng) whose presence is a realty in Montasik District, Aceh Besar. Therefore, this research tries to discuss about â€œDonation Giving after Paddy Harvest to Beggars in Montasik District Aceh Besarâ€. In general, the main profession of people in Montasik district is farmer. In terms of educational development, particularly in religious educational sector, it has been built the place to learn Islamic and Quranic Teaching for both male and female. The place is generally called Dayah.The aims of this research are to find out the factors causing the people in Montasik district gave donation to the beggars after paddy harvest. The method used was analytic descriptive approach and this research can be categorized as field research. The object of this research is Montasik District region which consists of 39 gampongs and the key informants were gampong leaders (Keuchik or its staff) and also the people considered could be representatives in data collection process. The techniques in collecting the data were through observation and interview. The sources of data were 15 keuchiks, 1 Camat, some people and villagerâ€™s staff considered could give data to the researcher. The findings of this research were the main factor causing people in Montasik district to give donation to the beggars especially after harvest process was they believed that it was part of Islamic teaching related to worship. According to Hadih Maja that they have believed from generation to generation, when giving donation to beggars it is not by seeing to the status of beggars whether they were prosperous than the givers or not. The content of Hadih Maja is: Bek Pesoh Jaro ( which means donâ€™t let anyone who begs donation go without taking anything), Bek Peputoh Asa (which means donâ€™t let them be hopeless because of not getting anything) because it is not suggested in the religious teaching and it can hurt the feeling of the beggars, Nyanke Ata Tanyo (which means according to Islam, what we have given to others, it is actually our reward in hereafter, while what we enjoy in the world will be useless, therefore in is important to save the supply for the sake of hereafter life). Then, many people considered that the upper hand (who gives the donation) is better than the lower hand (who accepts the donation) as what is taught in Islam so that they gave the beggars donation sincerely. After giving donation, they felt they have followed what Islam teaches and they felt happy to be able to help the others. However, if the beggars showed unhappy feeling when accepting a small number of donations from the people, they felt unhappy and intolerant to the beggars.